Determinants of Foreign Direct Investment Inflows in Algeria An Analytical Econometric Study (1980-2017). - بسدات, كريمة (مجلة الاستراتيجية والتنمية, 2019)
Abstract The study aims to determine the factors that affect the foreign direct investment inflows in Algeria, using a sample of 38 observation for the period 1980-2017.Rely on annual time series and multiple linear regression model to examine the relationship between foreign direct investment inflows as a dependent variable, andmarket size, trade openness, economic stability,credit provided by financial sector,human capital, political stability,quality of infrastructure as independent variables. The results show that market size, trade openness,human capital have a positive and significant effect on foreign direct investment inflows in Algeria. Keywords: FDI Inflows, Determinants of FDI, Algeria. JEL Classification: C25, F21